Assessing the effects of artificial gravity in an analog of long-duration spaceflight: The protocol and implementation of the AGBRESA bed rest study - Clément, Gilles; Rittweger, Jörn; Nitsche, Andrea; Doering, Wolfgang; Frings-Meuthen, Petra; Hand, Olga; Frett, Timo; Noppe, Alexandra; Paulke, Freia; Lecheler, Leopold; Jordan, Jens; Stern, Claudia; et al. (Frontiers in Physiology, 2022)
A comprehensive strategy is required to mitigate risks to astronauts’ health, well-being, and performance. This strategy includes developing countermeasures to prevent or reduce adverse responses to the stressors astronauts encounter during spaceflight, such as weightlessness. Because artificial gravity (AG) by centrifugation simultaneously affects all physiological systems, AG could mitigate the effects of weightlessness in multiple systems. In 2019, NASA and the German Aerospace Center conducted a 60-days Artificial Gravity Bed Rest Study with the European Space Agency (AGBRESA). The objectives of this study were to 1) determine if 30 min of AG daily is protective during head down bed rest, and 2) compare the protective effects of a single daily bout (30 min) of AG versus multiple daily bouts (6 × 5 min) of AG (1 Gz at the center of mass) on physiological functions that are affected by weightlessness and by head-down tilt bed rest. The AGBRESA study involved a comprehensive suite of standard and innovative technologies to characterize changes in a broad spectrum of physiological systems. The current article is intended to provide a detailed overview of the methods used during AGBRESA.